Porphyrin-based conjugated organic polymer with dual metal sites for highly active and selective visible-light-driven reduction of CO2 to CO. Issue 39 (16th September 2022) - Li, Jinyu; Hou, Yuxia; Cui, Cheng-Xing; Zhang, Xiupeng; Wang, Ji-Chao; Wang, Airong; Chen, Zhipeng; Li, Mingchang; Lou, Tianjun
Abstract : Porphyrin-based conjugated organic polymer with dual metal sites displaying high photocatalytic reduction activity for CO2 to CO without a sacrificial reagent and only H2 O. Abstract : A porphyrin-based conjugated organic polymer (COP) was constructed from 5, 10, 15, 20-tetrakis(4-bromophenyl)porphyrin copper (CuTBPP) and 5, 5′-bis-ethynyl-2, 2′-bipyridine (BPY) via Sonogashira coupling. Its complex Co/CuTBPP–BPY–COP (with dual metal sites composed of copper porphyrin and a cobalt BPY unit) was prepared by coordination with Co 2+ . All of the prepared CuTBPP–BPY–COP and Co/CuTBPP–BPY–COP compounds exhibited excellent photocatalytic performance toward CO2 reduction under visible-light irradiation without another sacrificial reagent but only H2 O. Co/CuTBPP–BPY–COP (dual metal sites) exhibited better photocatalytic activity than CuTBPP–BPY–COP (a single metal site). Co/CuTBPP–BPY–COP retained a higher photocatalysis capacity for CO2 reduction after 10 consecutive cycles. The total quantity of CO product was 263.2 μmol g −1 after 10 h of irradiation. Theoretical studies indicate that introducing Co metal centers and nitro groups are more favorable for the photoreduction catalysis of CO2 compared with that using CuTBPP–BPY–COP.